Analysis of ion radiation characteristics in the middle and late stages of laser-produced Cd plasma evolution in vacuum. (March 2021) - Bakhiet, Mohammedelnazier; Su, Maogen; Cao, Shiquan; Wu, Yanhong; Li, Maijuan; Dong, Chenzhong
Highlights: The EUV spectra of the middle and late stage of expansion of laser-produced Cd plasma were measured in the 8.5-12 nm region, using a spatiotemporally resolved laser-produced plasma spectroscopic technique. The 4p-6s resonance transition arrays from Cd 4+ to Cd 7+ ions dominate the spectrum, which has been identified with the aid of the Hartree-Fock (HF) method with relativistic corrections (HFR) using the Cowan codes. Several new spectral features were established for the first time and were tentatively assigned. Using the steady-state collisional-radiative model (CR), the plasma parameters have been obtained by comparing the experimental and simulated spectra, which have given the best agreement for the relative ion populations consistent with the observed spectra. The evolution behavior of the rate coefficients with an electron density and an electron temperature have been discussed in detail, and several physical aspects involving in plasma expansion were provided. Abstract: In this paper, the EUV spectra of the middle and late stage of expansion of laser-produced cadmium (Cd) plasma were measured using a spatiotemporally resolved laser-produced plasma spectroscopic technique. The 4p-6s resonance transition arrays from Cd 4+ to Cd 7+ ions dominate the spectrum, which has been identified with the aid of the Hartree-Fock (HF) method with relativistic corrections (HFR) using the Cowan suite of codes. Several new spectral lines were demonstrated for the first time and were tentatively assigned. Spectral simulations of the plasma expansion into a vacuum based on the assumption of a normalized Boltzmann distribution among the excited states associated with a steady-state collisional-radiative model were also carried out to obtain the plasma parameters by comparing experimental and simulated spectra. The dominant ion stages and the corresponding ion fractions for different ion stages were obtained. In addition, we have discussed in detail the evolution of the rate coefficients with electron density and electron temperature. Numerous physical aspects, including ion expansion energy, electron-ion thermalization time, plasma sound speed, electron plasma velocity and frequency, skin depth, as well as plasma coupling parameters were investigated. We have also found good agreements between experimental and theoretical synthetic spectra using excitation temperatures of 14 eV and 15.5 eV., . These results should be helpful for further spectral identifications in the fields of plasma diagnostics and nuclear fusion.